Recent Publications (Quarterly Journal of Economics, 1942)
Recent Publications Get access The Quarterly Journal of Economics, Volume 57, Issue 1, November 1942, Pages 163–167, https://doi.org/10.1093/qje/57.1.163 Published: 01 November 1942